Early identification of the opposition shot taker characterises elite goalkeepers` ability to read the game - Murphy, C. P.; Patel, K.; Hope, E.; North, J. S. (Science and Medicine in Football, 2025)
Researchers investigating expertise in soccer goalkeepers have overwhelmingly focused on anticipating penalty kicks and identifying kinematic cues that are used to anticipate action outcomes. In this study, we took a novel approach to exploring `game reading` skills in soccer goalkeepers. Specifically, we investigated whether and by what point during an attacking sequence in open play, elite goalkeepers can identify the opposition shot taker, a skill that is likely to facilitate organisation of the defensive line and interception of forward creative attacking passes. We used a moving window temporal occlusion paradigm to present elite, sub-elite, and amateur goalkeepers with 11-vs-11 attacking sequences that were divided into progressive segments. After viewing each segment, participants identified the player they thought would shoot at goal at the end of the attacking sequence. Elite goalkeepers identified the opposition shot taker earlier and more accurately than sub-elite and amateur participants. Findings suggest that elite goalkeeping is underpinned not only by anticipation of action outcomes but also game-reading skill that enables identification of the player most likely to carry out those actions.